Development of nursing quality evaluation indicators for extracorporeal membrane oxygenation based on Donabedian theory: A Delphi study - Xiaomei Yu; Huihuang Zou; Shuaihong Tong; Yong Zhang; Zhijun Tian; Shichao Zhu (PLoS ONE, 2025)
Extracorporeal membrane oxygenation (ECMO) serves as a vital therapy for refractory severe respiratory and circulatory failure. With its expanding application in China and the heightened demand for high-quality medical services, ensuring top-notch nursing care during ECMO treatment is crucial. However, existing ECMO nursing quality evaluation tools have limitations, such as lacking detailed calculation formulas for some indicators and insufficient scientific grounding due to over-reliance on expert experience. Thus, there is an urgent need to develop a scientific and practical index system for evaluating ECMO nursing quality to provide an objective basis for monitoring and improving care.This Delphi study was conducted to develop and refine quality indicators for ECMO care, adhering to ACCORD guideline. First, a literature review and expert discussions were carried out to design an expert questionnaire. Then, nineteen experts in critical care participated in two rounds of Delphi surveys. After the surveys, the analytic hierarchy process was employed to assign weights to the indicators.This study achieved a 100 questionnaire recovery rate, and there was high agreement among the experts. Through the two-round consultation, the final ECMO care quality indicators were determined, including three primary indicators, nine secondary indicators, and 32 tertiary indicators. A scientific and reliable ECMO care quality evaluation system was successfully created. This system offers a comprehensive basis for future assessments of ECMO care in China, addressing the need for robust quality evaluation tools in this field and contributing significantly to the continuous improvement of clinical nursing.